Theology and the End of Doctrine. - Helmer, Christine (Westminster John Knox Press, 2014)
Intro -- Contents -- Preface -- Source Abbreviations -- 1 Theology and Doctrine -- 2 From Ritschl to Brunner -- 3 From Trinitarian Representation to the Epistemic-Advantage Model -- 4 Language and Reality -- 5 Acknowledging Social Construction and Moving beyond Deconstruction -- Bibliography -- Index of Ancient Sources -- Index of Names -- Index of Subjects.